Morfologia de ovos de Dioctophyme renale Goeze, 1782 (Nematoda: Dioctophymatidae) e influência da temperatura no desenvolvimento de larvas de primeiro estágio nos ovos - Pedrassani, Daniela [UNESP]; Hoppe, Estevam Guilherme Lux [UNESP]; Avancini, Neuri; do Nascimento, Adjair Antonio [UNESP] (My University, 2009)
This study aims to provide information on morphological data of D. renale eggs, as well as on first-stage larvae development into eggs kept at different temperatures. Eggs were obtained by centrifugation of infected dog urine, placed in Petri dishes, and stored in BOD chamber for a 90-day period. Each treatment (GI - 15 °C, GII - 20 °C, and GIII - 26 °C) was repeated fve times. Eggs showed average measures of 67.23 × 42.78 μm, and the mean incubation time was inversely proportional to the incubation temperature. Larvae motility was observed one week after being observed in eggs.
Morphology of eggs of Dioctophyme renale Goeze, 1782 (Nematoda: Dioctophymatidae) and influences of temperature on development of first-stage larvae in the eggs
Keywords: Dioctophyme renale; Dog; Eggs; Temperature